Introduction to architecture - Ching, Francis D. K (Wiley, 2012)
Includes index; KR003 Kiến trúc nhập môn; A survey of the built environment distills the work of legendary author and illustrator Francis D. K. Ching into a single volume Introduction to Architecture presents the essential texts and drawings of Francis D. K. Ching for those new to architecture and design. With his typical highly graphic approach, this is the first introductory text from Ching that surveys the design of spaces, buildings, and cities. In an easy to understand format, readers will explore the histories and theories of architecture, design elements and process, and the technical aspects of the contemporary profession of architecture. The book explains the experience and practice of architecture and allied disciplines for future professionals, while those who love the beauty of architecture drawing will delight in the gorgeous illustrations included. Overview of the issues and practices of architecture in an all-in-one introductory text Includes new chapters and introductory essays by James Eckler, and features more than 1,000 drawings throughout Professor Ching is the bestselling author of numerous books on architecture and design, all published by Wiley; his works have been translated into 16 languages and are regarded as classics for their renowned graphical presentation For those pursuing a career in architecture or anyone who loves architectural design and drawing, Introduction to Architecture presents a beautifully illustrated and comprehensive guide to the subject